Biodiversity of Italian freshwaters: an updated checklist of mayfly species (Ephemeroptera) as a starting point for the next taxonomic (r)evolution - Buffagni, Andrea; Belfiore, Carlo (ZooKeys, 2025)
The study of biodiversity and ecosystems must be based on detailed knowledge of animal and plant organisms. European strategies for the protection of biodiversity and the restoration of natural environments advocate in-depth studies where knowledge is most lacking or fragmentary, in order to adequately assess relevant changes. Italian Ephemeroptera have not been the subject of specific taxonomic studies for approximately 30 years. This paper presents a list of the species currently thought to occur in Italy, which amounts, on the basis of morphology, to 106 species. Of these, approximately one-fifth are endemic species, demonstrating the importance of the Italian territory for European and Mediterranean biodiversity. The main critical aspects are discussed with reference to both the recent history of the study of Italian Ephemeroptera and the prospects for future development. The general picture shows that i) many species are insufficiently studied and known; ii) there are probably several new species to be described; iii) several endemic species described in the last decades or centuries require confirmation of validity and/or presence. Specific studies on mayflies will need to focus on these aspects in order to increase our knowledge of natural systems and enable their appropriate protection and restoration.